Toward Holistic Community Development: Implementing KKNT Strategies for Qur'anic Understanding and Community Engagement - Bahrul Ulum; Afifa Rahmasari; Cut Mawaddah Al-Mukarromah; Rozzatul Marzian; Saddiah; Khairul Anhar (As-sunnah: Jurnal Pengabdian Masyarakat, 2023)
Implementing KKNT initiatives in Meunasah Ar-Rahmah in Blang Kolak Village II serves a multifaceted purpose. The primary objective is to elevate the understanding of the Qur'an among individuals and address and rectify any misconceptions or errors that may have manifested in their actions. Concurrently, the initiative aims to foster a sense of communal involvement by encouraging productive endeavors that contribute to individual growth and enhance the overall Ramadhan experience for the surrounding community. To ensure the effective execution of these initiatives, KKNT employs a strategic approach known as ABCD (Asset-Based community development), which consists of five sequential steps: identification, strategizing, conceptualizing, decision-making, and implementation. The one who imparted knowledge of the Qur'an and the principles of Islam is the prophet Muhammad shalallahu ‘alaihi wa salam.